Sistem Pendukung Keputusan Rekomendasi Tempat Wisata Di Pulau Bawean Menggunakan Metode Analytical Hierarchy Process - Ainul Faris; Andrey Kartika Widhy Hapantenda (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Tourism is one of the sectors that is very influential in economic income and also the welfare of the people in Indonesia. Many tourists make considerations before determining which tourist attractions to go to through various criteria that match their wishes. This consideration becomes difficult if tourists do not know the criteria they want is in accordance with the conditions of the tourist attractions to be addressed or not. On Bawean Island there are still not many information systems that can help prospective tourists in providing relevant information and also in accordance with the criteria of prospective tourists. Based on these problems, a system is needed that can help tourists in determining tourist attractions. A decision support system using the AHP (Analytical Hierarchy Process) method can help prospective tourists who will visit Bawean Island by determining the level of importance of the criteria with 9 levels that have been provided in this application